Reconstruction of the perineal defect after abdominoperineal resection with vertical rectus abdominis myocutaneous (VRAM) flap versus primary direct closure: a single center retrospective cohort study - Kalev, Georgi; Büttner, Sylvia; El-Ahmar, Mohamad; Reißfelder, Christoph; Seyfried, Steffen; Vassilev, Georgi; Hardt, Julia (Langenbeck's archives of surgery, 2025)
The closure of the perineal defect following pelvic surgery that includes abdomino-perineal resection (APR) can often be challenging and remains an important issue given the reported high wound morbidity. The vertical rectus abdominis myocutaneous (VRAM) flap, which was proposed in the past as an alternative to direct closure (DC), enables the reconstruction of extensive perineal wounds. 184 consecutive patients who underwent abdominoperineal resection at tertiary university institution between January 2014 and June 2024 were included in this retrospective analysis. The aim of the study was to evaluate the outcomes of perineal wound reconstruction using a VRAM flap (n = 29) compared to DC (n = 155). The rate of overall perineal and abdominal wall wound complications did not differ significantly (p = 0.321 and p = 1.000, respectively). However, significantly more pelvic abscesses requiring CT-guided percutaneous drainage were observed in the DC-group (p = 0.048). Subgroup analysis of patients who underwent radiochemotherapy prior to surgery revealed lower incidence of severe perineal complications after VRAM flap reconstruction of the perineal defect (p = 0.037). The VRAM flap has proven to be a safe technique and should be considered especially for the reconstruction of extensive perineal defects following pelvic surgery.